2018
DOI: 10.3390/cli6020039
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Indian Ocean Tropical Cyclone Tracks by the Standard Deviational Ellipse

Abstract: Abstract:The standard deviational ellipse is useful to analyze the shape and the length of a tropical cyclone (TC) track. Cyclone intensity at each six-hour position is used as the weight at that location. Only named cyclones in the Indian Ocean since 1981 are considered for this study. The K-means clustering algorithm is used to cluster Indian Ocean cyclones based on the five parameters: x-y coordinates of the mean center, variances along zonal and meridional directions, and covariance between zonal and merid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…In the western North Pacific and North Atlantic, greater storm intensity is related to longer lifetimes (Kang & Elsner, 2015). Using cluster analysis, Rahman et al (2018) found that the storms with the highest LMI tend to occur over the warmer ocean regions that have the highest amount of potential energy available. This is opposite to global‐based observations by Frank & Young (2007), where, the high intensity storms from category 3 to 5 systems persist for the shortest duration (mean of 1.9–2.3 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the western North Pacific and North Atlantic, greater storm intensity is related to longer lifetimes (Kang & Elsner, 2015). Using cluster analysis, Rahman et al (2018) found that the storms with the highest LMI tend to occur over the warmer ocean regions that have the highest amount of potential energy available. This is opposite to global‐based observations by Frank & Young (2007), where, the high intensity storms from category 3 to 5 systems persist for the shortest duration (mean of 1.9–2.3 days).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics involving duration to attain LMI have not been investigated for the NH. In the SH, a possible reason for the different durations to achieve LMI observed (Figures 4 and 6), points to higher SSTs and a warm moist environment, which promote greater potential intensity and energy for sustaining a storm (Rahman et al, 2018; Schenkel et al, 2018). This is based on the statistically significant relationships found (in this study; Figure 4) between intensity, duration and SST, which is well known as a thermodynamic requirement for high intensity tropical cyclones (Bhaskaran et al, 2018; Emanuel et al, 2004; Wing et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed processing process is shown in Figure 2. The standard deviation ellipse [36,37] is useful to analyze the spatial and temporal variation of precipitation centers and the trend of spatial distribution of precipitation regions. The long axis and the short axis of the ellipse surface were output, as well as the direction of the ellipse.…”
Section: Land Cover Land Use Data and Precipitation Data Processingmentioning
confidence: 99%
“…Trajectory clustering contrasts with the moving cluster approach, where the moving object is of interest (vs. the movement itself). Examples of trajectory clustering include cyclone track clustering in different world regions (Ramsay et al, 2012;Rahman et al, 2018). Among other factors, the characteristics of the data used influences the choice of the spatiotemporal clustering method.…”
Section: Spatiotemporal Clustering Brief Backgroundmentioning
confidence: 99%